Implementasi Sistem Monitoring Pada Panel Listrik - Fenty Pandansari; Yohanes Sugiarto (Media Aplikom, 2017)
Electric voltage panel monitoring system is a system to monitor the performance of an electric voltage panel. This system is developed to keep track of data in an electric panel, i.e. voltage, current, and frequency. The monitoring process uses multiple sensors in order to read the existing data in the panel. ACS712 sensor is used to read the currents that flow in each phase of the voltage panel. The frequency sensor circuit is used to read actual frequency on one of the phase in the voltage panel. The result of the reading from those sensors will then be processed by microcontrollers so that the final result can be displayed on the computer. Microcontrollers used by this system are Arduino Nano and Arduino Mega, which both can be programmed using Arduino Software (IDE). The software application to show the result on the computer is developed using C#, especially for the user interface, and MySQL as the database management system. Keywords : monitoring , database, C#